(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:The importance of lead as a toxic metal and environmental pollutant has long been recognized to human and animal health. In Iraq, lead pollution was documented in Baghdad and in Sulaimaniya city. Objective:To explore the protective role of vitamin E alone or in combination with the amino acid methionine against lead acetate side effects on hematological parameters of adult male rabbits. Methods:Thirty male adult rabbits were divided equally into five groups four of them administered lead acetate for 90 days, as sub-chronic exposure, and the fifth was considered as control. Three of these groups were treated with Vitamin E and/or methionine for 90 days. At the end of experiment, blood and liver samples were collected for either hematological analysis or histopathological examination. Results:Lead caused a significant decrease in lymphocytes and erythrocyte indices; and a significant increase in reticulocytes and neutrophils. At the same time, Vit. E, alone or mixed with methionine, corrected these values to semi normal values. Conclusion:Decreased erythrocyte indices and reticulocytosis that is found in the present study, demonstrates regenerative anemia in rabbits that had administered lead acetate. Vitamin E, alone or mixed with methionine, was efficient in reducing the side effects of Lead on hematological parameters; while, methionine had little or no effect when administered alone against lead which may be attributed to the dose or duration of the treatment. Keywords:Lead; vitamin E; methionine; hematological changes